Local nearrings, their structure, and the GAP system - Raievska, I.; Raievska, M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 512.6We present an overview of the current state of research of finite local nearrings. In particular, it contains all recently obtained results on the classification of local nearrings.